2014
DOI: 10.1530/rep-14-0086
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mouse models in the study of reproduction: insights into GATA protein function

Abstract: For the past 2 decades, transgenic technology in mice has allowed for an unprecedented insight into the transcriptional control of reproductive development and function. The key factor among the mouse genetic tools that made this rapid advance possible is a conditional transgenic approach, a particularly versatile method of creating gene deletions and substitutions in the mouse genome. A centerpiece of this strategy is an enzyme, Cre recombinase, which is expressed from defined DNA regulatory elements that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 108 publications
0
31
0
Order By: Relevance
“…Consistent with this expression pattern, different genetic mouse models have begun to illuminate the complex and essential roles played by this transcription factor in the very first steps of gonadal development and later, for male and female fertility (Kyrönlahti et al 2011a,b, Manuylov et al 2011, Bennett et al 2012, Efimenko et al 2013, Hu et al 2013, Tevosian 2014. While these studies clearly established the essential nature of GATA4 in reproduction, understanding how GATA4 accomplishes these tasks, i.e., identifying its target genes and thus its mechanism of action, remains incomplete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this expression pattern, different genetic mouse models have begun to illuminate the complex and essential roles played by this transcription factor in the very first steps of gonadal development and later, for male and female fertility (Kyrönlahti et al 2011a,b, Manuylov et al 2011, Bennett et al 2012, Efimenko et al 2013, Hu et al 2013, Tevosian 2014. While these studies clearly established the essential nature of GATA4 in reproduction, understanding how GATA4 accomplishes these tasks, i.e., identifying its target genes and thus its mechanism of action, remains incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with its very early expression at the stage of coelomic epithelial thickening, conditionally Gata4-deficient XX or XY embryos do not initiate the formation of a genital ridge (Hu et al 2013). Elegant mouse models used by Tevosian et al, where the Gata4 gene was excised around the time of sex determination by gonadspecific Cre drivers, have shown that GATA4 is also essential for normal testicular and ovarian differentiation (reviewed in Tevosian (2014)). These crucial functions in early mammalian gonadogenesis necessitate not only GATA4 but also a functional cooperation between GATA4 and its transcriptional partner Friend of GATA 2 (FOG2/ZFPM2; Tevosian et al 2002, Manuylov et al 2008.…”
Section: Introductionmentioning
confidence: 93%
“…Ovarian development is promoted by complementation of the transcription factor FOXL2 (forkhead box L2) and RSPO1 (R-spondin homolog 1)/WNT4 (winglessrelated MMTV integration site 4)/β-catenin signalling in GATA4-expressing supporting cells , Tevosian 2014. During early ovarian development, proliferative GATA4-expressing cells activate expression of the cell cycle inhibitor p27KIP1 (p27) and FOXL2 as they form non-proliferative granulosa cells (Mork et al 2012, Rastetter et al 2014, Gustin et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In the testis, GATA-4 regulates SC differentiation and function and is required for proper interaction between these somatic cells and germ cells. 45,49,50 In the conditional knockout of GATA-4, the testis was atrophic, with impairment of spermatogenesis and loss of fertility. Most importantly, SCs exhibited altered morphology and had increased permeability at the blood-testis barrier, 45 consistent with an immature phenotype.…”
Section: 1338-40mentioning
confidence: 99%